Museu de Ciências Naturais PUC Minas e suas interações com o público escolar no espaço do educador : interface e apropriações recíprocas - Bianca Rezende Godói (2022)
Science museums represent an important space for scientific communication and dissemination not only for the general public, but also for schools. In the present work, we sought to investigate and understand aspects of the interactions between these two spaces. The PUC Minas Museum of Natural Sciences was chosen as a case study and analysis, given its prominence as an important science museum. Therefore, an attempt was made to answer whether it would be possible to enhance the museum-school association through the development of a didactic resource for use by educators at the Museum and visiting professors in the so-called Educator Space. The study made it possible to develop the resource entitled “Visit Map”, which after completion was analyzed from the perspective of its possible contributions in the planning of visits by schools. A research with a qualitative approach was carried out, which included in its methodology collective semi-structured interviews with teachers who had visited Espaço do Educador in the past. The experiences of the teachers interviewed with the Museum and Espaço do Educador were valued in order to recognize their comments and suggestions for modifying parts of the educational resource. In this way, the creation of a didactic resource that can be used by museum educators and be evaluated in the future regarding the objectives we propose for it is presented, which are: to facilitate the work of museum educators and teachers in preparing the visit, benefit the reception of schools by the Museum in the Educator's Space, to provide the reader with greater reflection on museum education, to encourage the participation and engagement of teachers who do not yet know the Museum. Thus, with this research and intervention, we sought to favor not only the Museum itself, with a new communication resource, but also the schools, as they will have the opportunity to plan and enrich the visit with such material, and, consequently, student learning. This work also brings together studies about this important Museum, which are still not numerous.